Hubungan antara Kemampuan Berinteraksi Sosial dengan Hasil Belajar - Fernanda, Mistio Mesa; Sano, Afrizal; Nurfarhanah, . (Konselor, 2012)
Abstract Social interaction is a relationship that is experienced by every individual, including students. With a good social interaction, students are expected to develop their potential. Growing potential with maximum yielded a satisfactory learning outcomes. Good learning results coupled with a good ability to interact socially too. For that purpose of this study was to examine the relationship between the ability of social interaction with the learning outcomes. This research method is quantitative correlation type.